Five‐Year Soil Respiration Reflected Soil Quality Evolution in Different Forest and Grassland Vegetation Types in the Eastern Loess Plateau of China. Issue 7 (4th March 2013) - Yan, Junxia; Chen, Liangfu; Li, JunJian; Li, Hongjian
Abstract: Soil CO2 efflux in forest and grassland over 5 years from 2005 to 2009 in a semiarid mountain area of the Loess plateau, China, was measured. The aim was to compare the soil respiration and its annual and inter‐annual responses to the changes in soil temperature and soil water content between the two vegetation types for observing soil quality evolution. The differences among the five study years were the annual precipitation (320.1, 370.5, 508.8, 341.6, and 567.4 mm in 2005–2009, respectively) and annual distribution. The results showed that the seasonal change of soil respiration in both vegetation types was similar and controlled by soil temperature and soil water content. The mean soil respiration across 5 years in the forest (3.78 ± 2.68 µmol CO2 m −2 s −1 ) was less than that in the grassland (4.04 ± 3.06 µmol CO2 m −2 s −1 ), and the difference was significant. The drought soil in summer depressed soil respiration substantially. The Q 10 value across 5‐year measurements was 2.89 and 2.94 for forest and grassland. When soil water content was between wilting point (WP) and field capacity (FC), the Q 10 in both types increased with increasing soil water content, and when soil water content dropped to below WP, soil respiration and the Q 10 decreased substantially. Although an exponential model was well fitted to predict the annual mean soil respiration for each single year data, it overestimated and underestimated soil respiration, respectively, in drought conditions and after rain for short periods of time during the year. The two‐variable models including temperature and water content variables could be well used to predict soil respiration for both types in all weather conditions. The models proposed are useful for understanding and predicting potential changes in the eastern part of Loess plateau in response to climate change. Abstract : The results indicate that the two‐variable models including temperature and water content variables could predict well soil respiration for both types at all weather conditions. The models are useful for understanding and predicting potential changes in response to climate change.